Wisdom, intelligence, and creativity synthesized - Sternberg, Robert J. (New York : Cambridge University Press, 2003)
Offers a critical review and summary of the best research available on human intelligence, arguing that in order to truly understand intelligence, educators must look beyond standard test scores and assess students' creative abilities.
Includes bibliographical references (p. 189-214) and index.
Adult
Keywords: Creative ability; Creative thinking; Intellect; Wisdom; Creative ability; Creative thinking; Intellect